PERANCANGAN INSTRUMENT MINIATUR MONITORING ARUS LISTRIK PLN - RIENI KALESTA SITANGGANG (Saintia Fisika, 2013)
Already designed miniaturized instruments for monitoring the electrical current to the input electrical current of2 A and 4 A, using some of the load instead of the customer. Instrument designed transformer email surrounded 1.2mm wire to detect the flow of microcontroller ATMega 8535 and completed the program to change the scale analogvoltage output transformer into a digital scale and then displayed on the PC in the form of graphs appropriateamount of electrical current used load, number of current is not used in the time scale, and the event of the use incurrent exceeds the electric current in the monitor will display